The effectiveness of the Project-Based Learning (PjBL) approach in teaching mathematical modeling at the elementary school level: A systematic literature review - Idham Kholid (Privietlab, 2026)
The development of mathematical modeling skills has become a critical competency in the elementary school mathematics curriculum; however, instructional approaches are often abstract and challenging. Project-Based Learning (PjBL) is proposed as a potential pedagogical framework for concretizing the modeling process through authentic projects. This Systematic Literature Review (SLR) aims to synthesize empirical evidence regarding the effectiveness, design, and implementation challenges of PjBL for teaching mathematical modeling in elementary schools. Following the PRISMA protocol, a systematic search was conducted across four databases (Scopus, Web of Science, Garuda, and Google Scholar) for empirical studies from the period 2015-2024, resulting in 17 articles. The synthesis shows that PjBL, when designed with contextual themes and supported by structured teacher scaffolding, effectively enhances both modeling competencies (particularly in problem formulation and validation) and student affective aspects (engagement, motivation, and self-efficacy). The main challenges are time management, student cognitive load, and teacher preparedness. The primary contribution of this review lies in its exclusive and systematic mapping of the convergence between PjBL and mathematical modeling, specifically at the elementary level, offering a holistic analytical framework that integrates cognitive and affective outcomes alongside implementation dimensions. In conclusion, PjBL is a promising approach for mathematical modeling learning in elementary schools, with significant implications for curriculum design, teacher professional development, and authentic-assessment practices. Future research should explore models for teacher development and their effectiveness in more diverse cultural contexts.